(untitled) (Nuntius Antiquus, 2008)
Ekphrasis oreuidentia is an important picture of affection which plays a significant role in poetry. This vivid and detailed description of an object or action makes what is being described emerge in order to provoke readers’ emotions, moving their passion through poetical representation. The article presents some of the linguistic resources used to build this affective picture in two different episodes of two epic poems: Aeneid by Virgil and Os Lusíadas by Camões.